THE REPRESENTATION OF POWER HEGEMONY IN THE COLONIAL AND NEW ORDER ERA IN 'BALADA SUPRI' NOVEL (REPRESENTASI HEGEMONI KEKUASAAN PADA ZAMAN KOLONIAL DAN ORDE BARU DALAM NOVEL 'BALADA SUPRI') - Syahrotul Latifah; Candra Rahma Wijaya Putra (Leksema: Jurnal Bahasa dan Sastra, 2020)
The purpose of this research is to describe the social structures and the forms of power as well as their repetition from colonial era to New Order. This study used a sociological approach to literature with the theory of power hegemony proposed by Gramsci. This research was a type of descriptive-qualitative research. The data in this research are narratives, dialogues, and monologues quoted from the novel Balada Supri written by Mochamad Nasrullah. The results of this research showed that in the colonial era, th social structure consisted of colonizer and colonized group whereas in New Order era, there were government official group, which was supported by the capital owner group, and ordinary people group. In regard with the form of power, colonial era showed the dominance of violence and hegemony that was countered by native resistance through violence sas well. Meanwhile, in New Order era, there appeared to be violence and hegemony dominance with the resistance in the form of hegemony over intellectuals. On the other hand, the social structure and the form of power in the colonial era, particularly the dominance of violence, still continued in New Order era and was termed as neocolonialism.